The Croton Plant Morphological Characteristics Diversity: Development of A Field Guide (Leaflet) for Morphometric Learning - Wambrauw, Hengky Lukas; Fahruddin, Devi Anggraini Vitri; Nunaki, Jan Hendriek; Nasir, Nur Indah Ririn Fitriani; Damopolii, Insar; Winarno, Nanang (Global Education Journal, 2025)
This research aims to compile and develop a frame of mind related to field guidance on croton plants in Morphometric courses. This is motivated by the absence of a specific field guide discussing croton plants, even though Morphometric courses require field practicum material. Documented the cultivars of croton plants (Codiaeum variegatum) spread across 4 districts in Manokwari and develop a field guide in the form of a leaflet of croton plant cultivars. The study was conducted using the ADDIE development model which is limited to 3 stages, namely Analysis, Design and Development. The subjects of the study were Biology Education Students. The research product was in the form of a croton plant leaflet that was validated by the material and media validator. Meanwhile, to test student responses, a questionnaire was used. The results of the UPGMA analysis grouped 26 cultivars into 3 groups, namely 6 narrow-leafed cultivars, 11 medium-leafed cultivars and 9 broad-leafed cultivars. This grouping is more influenced by leaf shape. The results of the analysis showed that there were 19 identical accessions (1.00). The results of the leaflet product validation for material experts were declared very valid (81.67%), and media experts were declared very valid (98.68%), in line with student responses stated as very practical (90.97%).